Potters of Hispanic terra sigillata with indigenous names (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This is the corpus of the local personal names testified in the potters’ stamps on Hispanic terra sigillata. These personal names prove the participation of natives in the manufacture of this ceramic tableware.
Keywords: Hispano-Celtic; Anthroponym; Reburrus; Tritium Magallum; Decknamen